Google sala de aula no ensino da Química do PCNA/UFPA Campus Universitário de Ananindeua - AMARAL, Joyce Leite do (2020)
This paper addresses the problem of dropout and failure in higher education in chemistry courses, a situation confirmed by the result of PISA (2018) for Brazil. In this context, the use of the Google Classroom tool was inserted in the Leveling Learning Program (PCNA) monitoring of the Ananindeua-PA University Campus, seeking to expand student service through the Blended Learnig learning modality linked to the leveling program. The applied methodology was based on Bloom's Taxonomy for traditional and inverted classroom. Among the results, 90% of respondents favored the insertion of the new online monitoring model, and considered the tool 71.4% quick and easy to use. The analyzes made were favorable regarding the leveling of the students, which contributed to the teaching-learning process of chemistry.